Optimal Control in Manufacturing Areas Increase the Productivity in the Aerospace Industry of Mexicali, Baja California, México - Rogelio Lopez Rodríguez; Juan Carlos Quiroz Sánchez; Alicia Lopez Ortiz; Juan Gabriel López Hernández; Olivia Yessenia Vargas Bernal, (Indian Journal of Management and Language (IJML), 2024)
The efficient control in the manufacturing control is very essential to increase the productivity and some specialized devices are made with and adequate functions. These devices are MEMS (Micro Electromechanical Systems), which are low-power microdevices widely used in the industrial processes of the Mexicali aerospace industry, which have the function of controlling the operation of industrial systems at any stage of manufacturing by evaluating the way to carry out their activities, comparing standardized values with data real and activate and deactivate high power actuator mechanisms such as fans, motors, electric pumps and other high power used in this installed industry. These microdevices have specific characteristics in their operation to obtain the best operational performance of industrial equipment and machines, at a low cost and partially operating according to the operating system reference values of industrial systems and generating a safe process in their operation. The industrial processes of the Mexicali aerospace industry require specialized knowledge because they manufacture components with very rigid operations because they are manufactured for aircraft with very rigorous regulations, due to the high security that air transport requires. MEMS have increased their use in the last ten years, where it has been applied to various industries due to the simple way of coupling with industrial systems, and this is why research was conducted to evaluate its use in a company in this city that they did not intend to use them and when observing that they increased their productive performance at one stage of their industrial processes, they chose to apply them in all their manufacturing areas. The investigation was from 2018 to 2019.